2021
DOI: 10.15585/mmwr.mm7039a2
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in COVID-19 Vaccination Status, Intent, and Perceived Access for Noninstitutionalized Adults, by Disability Status — National Immunization Survey Adult COVID Module, United States, May 30–June 26, 2021

Abstract: Estimates from the 2019 American Community Survey (ACS) indicated that 15.2% of adults aged ≥18 years had at least one reported functional disability (1). Persons with disabilities are more likely than are those without disabilities to have chronic health conditions (2) and also face barriers to accessing health care (3). These and other health and social inequities have placed persons with disabilities at increased risk for COVID-19-related illness and death, yet they face unique barriers to receipt of vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 6 publications
3
43
0
Order By: Relevance
“…[1][2][3] Making Covid-19 vaccines available does not necessarily lead to a very large population vaccine coverage, as shown by the percentages of people who are still not vaccinated in Western countries [4], even when these vaccines are free. Recent studies in the UK, in the US and in Norway [5][6][7][8][9][10] have shown that the most socially disadvantaged and racialised social groups are the least vaccinated. In light of their high risk of infection and mortality from Covid-19 [1], it appears all the more important to understand why they are less likely to be reached by Covid-19 vaccine programmes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Making Covid-19 vaccines available does not necessarily lead to a very large population vaccine coverage, as shown by the percentages of people who are still not vaccinated in Western countries [4], even when these vaccines are free. Recent studies in the UK, in the US and in Norway [5][6][7][8][9][10] have shown that the most socially disadvantaged and racialised social groups are the least vaccinated. In light of their high risk of infection and mortality from Covid-19 [1], it appears all the more important to understand why they are less likely to be reached by Covid-19 vaccine programmes.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent serious illness and death, it is important that all persons in the United States, including those in the LGBT community, stay up to date with recommended COVID-19 vaccinations. NIS-ACM collects data from adults aged ≥18 years using a random-digit-dialed sample of cellular telephone numbers (3). Data collected during August 29-October 30, 2021 from 153,062 respondents were weighted to represent the noninstitutionalized U.S. adult population and to match the number of adults who received ≥1 dose* of COVID-19 vaccine as reported by jurisdictions to CDC.…”
mentioning
confidence: 99%
“…Given that individuals with disabilities have been found to be differentially impacted by the COVID-19 pandemic [ 12 14 ], individuals with moderate-to-severe TBI may be susceptible to direct and/or indirect effects of the COVID-19 pandemic. However, few studies to date have investigated how the pandemic has affected persons with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with disabilities have historically faced barriers to accessing healthcare, resulting in health inequity, particularly among racial/ethnic minority groups [ 10 ]. The COVID-19 pandemic has magnified these longstanding inequities [ 11 ]; persons with disabilities are at higher risk of serious illness secondary to underlying neurologic conditions [ 12 , 13 ] and have more difficulty engaging in COVID-19 preventative measures [ 14 ]. Persons with traumatic brain injury (TBI) represent an estimated 11.4 million persons with disability [ 15 ] who may be particularly affected by the pandemic, though currently only one cross-sectional study exists on how the COVID-19 pandemic has affected TBI survivors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%